2022
DOI: 10.3390/biomedicines10020446
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Rho-Associated Protein Kinase-Induced Brain Changes in Vascular Dementia

Abstract: Patients with vascular dementia, caused by cerebral ischemia, experience long-term cognitive impairment due to the lack of effective treatment. The mechanisms of and treatments for vascular dementia have been investigated in various animal models; however, the insufficient information on gene expression changes that define pathological conditions hampers progress. To investigate the underlying mechanism of and facilitate treatment development for vascular dementia, we established a mouse model of chronic cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 58 publications
(81 reference statements)
2
13
0
Order By: Relevance
“…Surgical intervention can simulate vascular dementia, the second most common neurocognitive disorder. Employing bilateral carotid artery stenosis in mice, Lee and colleagues reported that pro-inflammatory cytokines, rho-associated protein kinase, and mRNA levels of blood–brain barrier-related tight junction proteins were decreased; smooth muscle alpha-actin positive vessels were increased, cortex cell rearrangement was decreased, and microtubule-associated protein-2-positive neural cells was decreased in the hippocampus, simulating the clinical pathology of vascular dementia [ 39 ]. Thus, this model ensures high face validity.…”
mentioning
confidence: 99%
“…Surgical intervention can simulate vascular dementia, the second most common neurocognitive disorder. Employing bilateral carotid artery stenosis in mice, Lee and colleagues reported that pro-inflammatory cytokines, rho-associated protein kinase, and mRNA levels of blood–brain barrier-related tight junction proteins were decreased; smooth muscle alpha-actin positive vessels were increased, cortex cell rearrangement was decreased, and microtubule-associated protein-2-positive neural cells was decreased in the hippocampus, simulating the clinical pathology of vascular dementia [ 39 ]. Thus, this model ensures high face validity.…”
mentioning
confidence: 99%
“…Preclinical translational animal studies play a major role in neuroscience research to understand the roles of neuropeptides, neurohormones, and endogenous biomolecules in the normal function of human life such as cognition, emotion, and social interaction, and in pathological alterations developing into neurological and psychiatric disorders [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97]. Various bioactive molecules are synthesized in the Try-KYN metabolic system.…”
Section: Discussionmentioning
confidence: 99%
“…NO production of eNOS inhibited by ROCK ultimately reduces the cGMP of VSMCs, thereby constricting blood vessels. In animal experiments of the VD model, an increase in ROCK expression was shown [ 60 ].…”
Section: Rho-associated Protein Kinase (Rock) and Dementiamentioning
confidence: 99%